Models for solid oxide fuel cell systems : exploitation of models hierarchy for industrial design of control and diagnosis strategies /: exploitation of models hierarchy for industrial design of control and diagnosis strategies. ([2016]) - Marra, Dario; Pianese, C (Cesare); Polverino, Pierpaolo; Sorrentino, Marco
No abstract available